Evaluation of Entrepreneurship Internships for Social Sciences Education Students at the Al-Fatimah Islamic Boarding School, Bojonegoro - Sukma Perdana Prasetya (UIN Fatmawati Sukarno Bengkulu, 2024)
This research helps develop a business model for micro-enterprises in Islamic boarding schools that involves students in studying how Islamic boarding schools can integrate entrepreneurial activities with the religious and social education they provide. The main aim of this research is to evaluate entrepreneurial internship activities based on the responses of students who have carried out internship activities at the Al-Fatimah Bojonegoro Islamic Boarding School Micro Enterprise. The subjects of this research were ten students from the Social Sciences Education Study Program at Surabaya State University who took part in the 2023 Matching Fund program. Quantitative descriptive research method. Data collection was carried out through surveys using questionnaires and interviews, which were then tabulated, and percentages were analyzed and described qualitatively. The results of this research do not have an impact on aspects of study, curriculum, and professional competence because they do not match the profile of the main graduate, namely being a prospective social studies teacher, but are practically able to increase knowledge and experience in entrepreneurship. In the aspect of personal skills and entrepreneurial skills, students positively assess the entrepreneurial internship program so that through direct practice, it can open new insights into entrepreneurship for students. The results of this research contribute to the development of social science by presenting a concrete case study of how economic, social, and religious aspects are interrelated in an entrepreneurial internship activity.